2021
DOI: 10.30564/jaeser.v4i2.3128
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Management Research of a Large-span Continuous Rigid Frame Bridge Based on Reliability Assessment by Using Strain Monitored Data

Abstract: When the bridge components needing maintenance are the world problem at present, and the health monitoring system is considered to be a very helpful tool for solving this problem. In this paper, a large number of strain data acquired from the structural health monitoring system (SHMS) installed on a continuous rigid frame bridge are adopted to do reliability assessment. Firstly, a calculation method of punctiform time-dependent reliability is proposed based on the basic reliability theory, and introduced how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In the paper, the data acquired from the sensors named 2-3MID-1, 2-3MID-2, 5-6MID-2, 4Z9h-1 and 4G1h-1 are taken as samples to display the profile of the monitoring data, and the selected time period is from March 2006 to April 2010. The pre-processed method of transforming the initial data into strain data is elaborated in detail in the papers [22,23] . Figure 4 shows the outline of the strain data after several pre-processed steps.…”
Section: The Monitoring Data Processingmentioning
confidence: 99%
“…In the paper, the data acquired from the sensors named 2-3MID-1, 2-3MID-2, 5-6MID-2, 4Z9h-1 and 4G1h-1 are taken as samples to display the profile of the monitoring data, and the selected time period is from March 2006 to April 2010. The pre-processed method of transforming the initial data into strain data is elaborated in detail in the papers [22,23] . Figure 4 shows the outline of the strain data after several pre-processed steps.…”
Section: The Monitoring Data Processingmentioning
confidence: 99%
“…As for the prestress loss and concrete shrinkage and creep etc., the load effects σ S distribution gradually close to concrete tensile strength distribution with time, therefore, we calculate the initial quasi dynamic reliability q β by using the quasi dynamic tensile strength distribution as the the resistance σ R . The method of quasi dynamic load effects σ S transferred from the monitored data and initial quasi dynamic reliability q β calculation step both can be seen in the papers [18,19] . Figure 5 illustrates the quasi dynamic load effects σ S distribution.…”
Section: The Calculation Of the Initial Quasi Dynamic Reliability Q βmentioning
confidence: 99%
“…Gao 29 studied the probability model of the extreme effect of traffic load during service period based on the health monitoring data of bridge structure. In order to evaluate the reliability of continuous rigid frame bridge, Li 30 found that the probability density function of stress effect of concrete bridge followed normal distribution.…”
Section: Introductionmentioning
confidence: 99%